Figure 6 from: Haukisalmi V, Konyaev S, Lavikainen A, Isomursu M, Nakao M (2016) Description and life-cycle of Taenia lynciscapreoli sp. n. (Cestoda, Cyclophyllidea). ZooKeys 584: 1-23. https://doi.org/10.3897/zookeys.584.8171 - Haukisalmi, Voitto; Konyaev, Sergey; Lavikainen, Antti; Isomursu, Marja; Nakao, Minoru (Zenodo, 2016)
Figure 6 - Large and small rostellar hooks of Taenia lynciscapreoli sp. n. from Lynx lynx, the higher picture showing the characteristic ridge and pits of large hooks. Scale-bars: 50 μm.